Relative Lengths of Paths and Cycles in 2-Connected Graphs - Nkoghosyan, Zhora G. (Mathematical Problems of Computer Science, 2021)
Let l be the length of a longest path in a 2-connected graph G and c the circumference - the length of a longest cycle in G. In 1952, Dirac proved that c , by noting that "actually c , but the proof of this result, which is best possible, is rather complicated". Let L1;L2; :::;Lm be a vine on a longest path of G. In this paper, using the parameter m, we present a more general sharp bound for the circumference c including the bound c as an immediate corollary, based on elementary arguments.